2018
DOI: 10.1007/s12350-016-0767-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pharmacological stress agent on patient motion during rubidium-82 myocardial perfusion PET/CT

Abstract: The choice of stressing protocol impacts significantly on patient motion. Patients stressed with regadenoson have significantly lower motion scores than those stressed with adenosine, using local protocols. This motion is more likely to be associated with a drift of the heart away from a baseline position, coinciding with the termination of infusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
44
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 25 publications
2
44
0
Order By: Relevance
“…We believe this may originate from changes in the patients breathing patterns during pharmacological stressing, with different patterns and magnitudes seen for different stress pharmaceuticals and infusion durations. 8,9 While the authors' conclusions suggest that motion in early frames is most important, we believe that whether motion occurs in early or late phases of the scan may simply be relative. If the reference segmentation is derived from late images, it is quite feasible to interpret that motion is in the early phase, and therefore an analysis of the differential motion (frameto-frame) would perhaps be more insightful.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…We believe this may originate from changes in the patients breathing patterns during pharmacological stressing, with different patterns and magnitudes seen for different stress pharmaceuticals and infusion durations. 8,9 While the authors' conclusions suggest that motion in early frames is most important, we believe that whether motion occurs in early or late phases of the scan may simply be relative. If the reference segmentation is derived from late images, it is quite feasible to interpret that motion is in the early phase, and therefore an analysis of the differential motion (frameto-frame) would perhaps be more insightful.…”
mentioning
confidence: 91%
“…The type and cause of patient motion is generally either periodic physiological sources such as respiratory motion, or more random effects such as in response to the effects of vasodilator stress agents, 8,9 or actual physical movements of the patient. Respiratory motion effects and to some extent physical movements of the patient may be automatically corrected by data-driven techniques 10 however this is likely to be particularly challenging in the case of dynamic PET using shortlived tracers.…”
mentioning
confidence: 99%
“…The motion magnitude and timing difference in the stress study could be explained by the use of a different vasodilator. 15 In Ref. 15, patients stressed using 20 seconds-injected regadenoson was found to have a significantly lower amount of motion as compared to those with adenosine infused over several minutes.…”
mentioning
confidence: 99%
“…15 In Ref. 15, patients stressed using 20 seconds-injected regadenoson was found to have a significantly lower amount of motion as compared to those with adenosine infused over several minutes. The current study 1 used regadenoson while 7 used dipyridamole.…”
mentioning
confidence: 99%
“…Overall, Koenders et al and others have made a valuable contribution to the literature highlighting the importance of blood pool phase patient motion during MBF measurements. 11,12 Recently, Memmott et al have shown that patient motion is more common with adenosine compared to regadenoson and hypothesized that patient motion may be most pronounced at termination of the adenosine infusion. 11 In addition, Lee et al demonstrated that blood phase motion in the inferior direction resulted in mean MBF and MFR errors of 29-44% in the RCA territory, 12 results consistent with the current manuscript.…”
mentioning
confidence: 99%